Characterization, sources, and ecological hazards of polycyclic aromatic hydrocarbons in the intertidal sediments of Zhelin Bay, the biggest mariculture area on the eastern Guangdong coast of China. (May 2018) - Gu, Yang-Guang; Ke, Chang-Liang; Liu, Qi
Abstract: Distribution characteristics, potential sources, and possible biological hazards of polycyclic aromatic hydrocarbons (PAHs) were examined in intertidal surface sediments of Zhelin Bay, the biggest mariculture base of eastern Guangdong Province, Southern China. The total PAH concentrations ranged from 8.05–51.32 ng/g (dry weight) with an average of 29.23 ng/g, which is beneath the documented concentrations in intertidal sediments gathered from various bays across the globe. The composition of PAHs was distinguished by high molecular weight (HMW, 4–6 rings) PAHs, with phenanthrene (PHE), fluoranthene (FA), and benzo(b)fluoranthene (BbFA) established as predominant components. Principle component analysis along with multivariate linear regression discovered that liquid fossil fuel combustion and coal/wood combustion contribute to 60.23% and 39.77% of PAHs in Zhelin Bay's intertidal sediments, respectively. Overall, surface sediments of Zhelin Bay have an 8% increased incidence of adverse biological effects due to PAH contamination, based on the mean probable effect level quotient. Highlights: PAHs and ecological risk in the intertidal sediments of Zhelin Bay were investigated. The high molecular weight (4–6 rings) PAHs predominated. Two emission sources were identified by PCA coupled with MLR. The sediments had a 8% probability of toxicity.